The History and Values Contained in Corak Insang Weave in Pontianak Malay’s - Muhammad Tisna Nugraha; Kartini Kartini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2018)
Pontianak Malay’s society is not only limited to the Malay ethnic group who lives near the Kapuas River, but they also have a tradition that is created from the habit and Islamic learning. This paper is initiated by the study that has been conducted by the researchers in 2016 implementing qualitative descriptive method. The data collection tools consist of observation, documentation and interview. The reason for choosing this method is to discover and reveal the meaning or the ideology of the symbols contained in the corak insang weave. Based on the results of this study, it is concluded as the first conclusion that the process to make corak insang weave needs sufficient time about one week. Corak insang weave can be formed in the manufacture of other woven fabrics, through the patches weave method, songket and bundle weave. The second conclusion shows that it is unfounded that a lot of physical evidence and historical documents or from sources are related to the meanings contained in Pontianak corak insang weave motive.